The Influence of Net Profit Margin, Return on Assets, and Earnings per Share on Stock Price with Debt to Equity Ratio as a Moderating Variable in the Basic Materials Secto - Ifan Pradipra Alamsyah; Fuad Ramdhan Ryanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of Net Profit Margin (NPM), Return on Assets (ROA), and Earnings per Share (EPS) on stock prices in companies within the Basic Materials sector, with Debt-to-Equity Ratio (DER) as a moderating variable. The research uses a quantitative approach with an associative type of study. Secondary data were obtained from the annual financial statements of companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The testing was conducted through Moderated Regression Analysis (MRA), preceded by classical assumption tests. The analysis results show that in the first model, the relationship between NPM, ROA, and EPS with stock prices is moderately strong, with a correlation value of 0.557 and a coefficient of determination of 31%. When DER is included as a moderating variable in the second model, the relationship becomes strong, with a correlation value of 0.670 and the coefficient of determination increases to 44.9%. Simultaneously, NPM, ROA, EPS, and DER along with their interaction terms significantly influence stock prices. The results indicate that NPM, ROA, and EPS each have a positive and significant partial effect on stock prices. DER also has a positive and significant effect. However, the moderating interaction results show that DER significantly moderates the relationship between NPM, ROA, and EPS on stock prices in a negative direction. This means that a higher DER weakens the positive influence of these three financial ratios on stock prices. These findings highlight the importance of optimal capital structure management to avoid diminishing market perceptions of a company’s value. The results suggest that optimal capital structure and operational efficiency are key factors in shaping market perception of firm value.